Konsep Kafaah dan Keluarga Sakinah (Studi Analisis Tentang Korelasi Hak Kafa’ah Terhadap Pembentukan Keluarga Sakinah) - Imam Syafi'i (Fakultas Syariah Institut Ilmu Keislaman Zainul Hasan, 2020)
Abstract This research aims to examine the realization of a peace family with the equivalent rights for married couples. Problems that arise, whether there is equality for husband and wife, related to peace in his marriage. the method used in this research is descriptive qualitative research which type library research. Where this author analyze the concep of kafa’ah and a peace family in documents form of a yellow books, reference, journal and other print media. Peaceful family can be achieved with the efforts of each partner in building a household. Peaceful family done after a marriage bond and will arise because there is a sense of belonging for husband and wife. Anyone and anytime without being bound by the necessity of equality between husband and wife. Keywords: marriage ties, equality rights, peaceful family.